O AEE e o atendimento ao aluno com autismo - Lobato, Debora Taiane Ferreira (Brasil, 2020)
This paper deals with a topic currently very visible and discussed by researchers who study in depth about autism, in order to clarify some issues on the subject. Autism is a developmental disorder that usually arises by age three and occurs in approximately two to seven out of every 1,000 individuals. Authors such as Maleval (2017), Mantoan (2003), Ropoli (2010), Costa (2017) among others, seek through their research to broaden these studies, also directing them to the regular classroom, because this is where they are. the biggest challenges in dealing with autistic children. This research assumed this assumption of verifying how the work with autistic students is developed in the public schools. Thus, we outline as general objective: Understand the ESA, from the use of the resource room, in the care of students with autism. And as specific: Identify teachers' challenges in performing their work in the resource room; Describe the actions developed to assist the student with autism; Know how the resource room is organized to meet diversity in special education and Recognize the importance of the resource room for the ESA, considering the needs of students. Thus, this work took a qualitative approach, using for data analysis the semi-structured questionnaire applied with teachers working in multifunctional resource rooms inserted in public schools in the city of Humaitá-AM that allowed us to understand the importance of educational care (ESA) for the autistic student, so that it contributes positively to the educational process of students with special educational needs, also allowed us to know how this care is developed, its specificities and how important is the family's role in their lives. students who need this service.